Some Aspects of the Problem of Bird Protection From Electrocution on Overhead Power Lines in Kazakhstan - Mark V. Pestov; Nurlan Kh. Ongarbaev (Пернатые хищники и их охрана)
The problem of mass death of birds of prey from electrocution on overhead power lines (PL) of medium power (6–10 kV) in the territory of Kazakhstan is well known since the times of the USSR and is still relevant. Our team has been dealing with this problem since 2010 (Saraev, Pestov, 2011; Pestov et al., 2012, 2015, 2019, 2021). Over the past years, we have repeatedly encountered various aspects of this problem and observed the consequences for ornithofauna from the use of certain technical solutions in the design, construction, operation, and reconstruction of PL. The present report is devoted to a brief review of some options of technical solutions in equipping PL in Kazakhstan.